IMAGING DIAGNOSIS—TRAUMATIC ABOMASITIS CAUSED BY FOREIGN BODIES IN A COW. Issue 6 (4th May 2016) - Constant, Caroline; Francoz, David; Babkine, Marie; Desrochers, André
Abstract : A 2‐year‐old Holstein cow presented with a history of colic signs of 3 days' duration that had not responded to routine medical therapy. Physical examination findings were consistent with tachycardia and colic. Ultrasonographic examination of the abomasum revealed a thin hyperechoic line producing a cone shadow. Radiography of the cranial abdomen revealed two radiopaque objects within the abomasum. Right paracostal laparotomy and abomasotomy permitted palpation and manual removal of two metallic foreign bodies and a small quantity of gravel. The animal recovered well after surgery and no signs of colic were observed. Her appetite and rumination were also improved.